Workplace hostility: defining and measuring the occurrence of hostility in the workforce - Selden, Meridith Pease; Downey, Ronald G. (My University, 2012)
Objectives: The purpose of this study was to define a comprehensive construct, workplace hostility, encompassing sub-areas of harmful workplace behaviors. Key characteristics include: perception of the target, persistence, intentionality, nonphysical nature, and organizational affiliation. Participants: Pilot study participants (N=42, students and N=35, workers) were small convenience samples. Main study participants (N=393, 70% female) were working individuals and almost 50% reported 1 to 5 years in their current jobs. Methods: The two pilot studies collected surveys face-to-face. The main study used online surveys. Results: Based on the pilot studies, items from the Workplace Hostility Inventory (WHI) were judged as a reasonable set. Results from the main study suggested three subscales related to perceptions of being subjected to hostility: interference with work, denigration, and exclusion. Supervisors produced greater distress on all factors, but only exclusion predicted a desire to leave the organization. Distress was greater when the perpetrator was a woman or a group. After controlling for feelings toward coworkers and supervisors, WHI was not related to job satisfaction. Conclusions: The WHI was found to be an inclusive construct, representing numerous concepts. The WHI is comprehensive and global, encompassing the previous overlap in existing research.
Keywords: Abuse; Job satisfaction; Job violence; Toxic behavior